Contradistinctive floral attributes, pollination guilds and their consequence on the outcrossing rate in two elevational morphs of Rhododendron arboreum Sm. - Sorokhaibam, Sachin Singh; Chandra, Atika; Baishya, Ratul; Barik, Saroj Kanta; Goel, Shailendra; Tandon, Rajesh (Frontiers in Plant Science, 2024)
Infraspecific floral trait variations may appear in response to elevational differences in alpine plant species. There is enormous information on the selection of such morphs mediated by biotic and/or abiotic variables. Whether such differences contribute to differences in reproductive strategy and mating outcomes is rarely investigated. We investigated these aspects in two distinct elevational floral morphs (Red and Pink) of Rhododendron arboreum Sm. in Western Himalaya. The red morphs occupy the lower elevations while pink morphs the higher elevations. The two morphs differ in floral traits like phenology, dimension, display, quality of floral rewards, and pollinators that happen to influence interaction with available pollinator pool at each elevation. The pink morph exhibits entomophily, while the red ones show ornithophily. Although experimental pollinations established that both the morphs are self-compatible, selfing results in significantly lower fruit-set than either cross-or open-pollinations. The outcrossing rate in the red morph, as determined by using simple sequence repeat (SSR) markers, was higher (tm=0.82) than that in the pink morph (tm=0.76), with a tendency of the latter to be shifting towards mixed-mating strategy. However, the extent of biparental inbreeding was comparable among the two morphs. It is inferred that the differences in the mating outcomes among the morphs in the tree species are linked to those emerging from floral traits and the pollination by different functional groups of floral visitors.